The Design and Synthesis of Light Responsive GSK-3 Inhibitors - Clotworthy, Megan (Auckland University of Technology, 2023)
The inhibition of kinase enzymes has proven to be a valuable therapeutic approach for the treatment of various diseases (such as cancer, cellular metabolism and neurodegenerative disorders). Despite the large number of potent kinase inhibitors reported in the literature, many of these typically bind to multiple kinase targets and exhibit poor tissue selectivity, giving rise to undesired side effects. The idea of creating selective drugs has proven difficult, as once a drug is administered, there is very little control over when and where the drug is active within a biological system. The implementation of photopharmacology (the use of light to control the biological activity of a drug) into drug design and development could prove to be useful in developing molecular tools with improved tissue selectivity. Through the use of photocages, known drugs can be modified to be inactive. Only once administered to the cellular setting is the caged inhibitor exposed to a selected wavelength of light, liberating the active form of the drug at the desired target. This project focusses on the development of photocaged glycogen synthase kinase 3 (GSK-3) inhibitors through the introduction of fluorescent caging groups onto a key binding moiety. This project firstly entails the successful synthesis of a known GSK-3